دراسة سوسيولوجية لظاهرة الفساد الإداري - خريبش, عبد القادر; بن قبي, آمنة (University of Eloued جامعة الوادي, 2015)
نحاول من خلال هذا المقال تناول موضوع شائك يختص بظاهرة الفساد الإداري؛ فنعرفه ونحدد أشكاله وتقديم المنظور الإسلامي في مكافحته، باعتبار أن الفساد الإداري لا يمكن أن يتحقق إلا على حساب المصلحة العامة، أو على حساب الآخرين، وإذا ما استشرى فإن الأمر قد يصل في بعض الأحيان إلى درجة يضطرب فيها المجتمع، وتتضرر المصلحة العامة، لأن الفساد من أسباب انعدام المساواة وفقدان العدالة، مما يؤدي إلى تولد الأحقاد والظلم الاجتماعي، وهذا بحد ذاته آفة خطيرة قد تهدد بالانهيار، لاسيما في الوقت الحالي الذي تعقدت في الحياة الاجتماعية وتغيرت الكثير من الاتجاهات، مما جعل تحقيق المنافع بحد ذاتها هدفاً يسعى إليه الكثيرون، وعمد البعض إلى طرق شتى لتحقيق ذلك، وعلى رأس هذه الطرق الفساد الإداري، بذلك أصبح موضوع دراسته ومكافحته قضية مركزية في معظم الدول، وحظي باهتمام الدارسين والباحثين في العلوم الإدارية والاقتصادية والقانونية. Sociological study of the phenomenon of corruption Abstract: We are trying through this article dealing with a thorny issue regard the phenomenon of administrative corruption; defining and determining the forms and submitting the Islamic perspective in combat, given that corruption can only be achieved on account of public property, or on account of others, and if it has spread, the command may arrive at some often to the point where the disturbed society, and harmed the public property, because the corruption of the causes of inequality and the loss of justice, leading to generate hatred and social injustice, and this in itself is a serious pest may threaten to collapse, especially at this time, which is complicated in social life and changed a lot of trends , making the realization of benefits in itself a goal sought by many, and some mayors to various ways to achieve this, and on top of these methods of administrative corruption, it has become the subject of study and control a central issue in most countries, and got the attention of students and researchers in the administrative, economic and legal sciences.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: لظاهرة السوسيولوجية - الفساد الإداري